Evaluation of Physical Education After The Covid 19 Pandemic at Private Vocational High Schools in Kroya District, Regency - Tyas Ghosaly; Bambang Priyono; Fajar Awang Irawan (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
Physical education is a required subject in schools because it is a component of the curriculum. This study's objectives are to evaluate the antecedents, transactions, and outcomes at private vocational schools in Kroya District, Cilacap Regency in 2022. In Kroya District, Cilacap Regency, school principals, PE teachers, and SMKS students provided the data for this study. Data collection techniques are observation, interviews, documentation. The obtained data was analyzed using the steps of data collection, data reduction, data presentation, and conclusion drawing. The teacher effectively implemented the PE learning strategy after the Covid-19 pandemic by preparing materials and learning strategies in the field. After the covid 19 pandemic, the time required to adapt to other learning presented a barrier to PE learing. Two hours were spent on the PE learning implementation transaction following the Covid-19 pandemic. Good describes the infrastructure at Kroya District Vocational High School. Kroya District Vocational High School's post-covid-19 pandemic lesson plan resulted in significant concern regarding the implementation of post-covid-19 pandemic education. From the three evaluations, it can be concluded that the implementation of post-pandemic PE learning at the Kroya District Vocational High School is not hindered by any of the existing obstacles.